Revisiting barriers to implementation of bioinformatics into life sciences education - Drew, Jennifer; Morgan, William; Galindo, Sebastian; Kleinschmit, Adam J.; McWilliams, Mindy; Pauley, Mark; Triplett, Eric W.; Williams, Jason; Murdoch, Barbara; Rosenwald, Anne (Frontiers in Education, 2023)
Bioinformatics is an interdisciplinary field at the intersection of computational and biological sciences that focuses on the analysis and interpretation of large biological data sets. Although recognized as essential in the life sciences, bioinformatics is not commonly integrated in undergraduate life science education programs. Based on a national survey in 2016, the Network for Integrating Bioinformatics into Life Sciences Education (NIBLSE) published a community-sourced set of core competencies in bioinformatics education. The survey also identified barriers that prevent incorporation of these competencies into the curriculum. In the current study, the NIBLSE group reports the findings of a new survey to 509 life science educators across the US in 2022 to identify current barriers of bioinformatics integration and to determine if the landscape of bioinformatics education has changed since the 2016 survey. Similar to previous results, a majority of respondents who currently teach bioinformatics or plan to teach bioinformatics report barriers. The top two barriers reported are students lacking prerequisite skills/knowledge and instructors lacking time to restructure course content. As in 2016, women reported experiencing barriers to bioinformatics teaching significantly more often than men; faculty from underrepresented minority backgrounds reported barriers more often than non-URM faculty; and educators at minority-serving institutions (MSIs) reported barriers more frequently than colleagues at non-MSIs. For additional insight into the barriers facing these educators, we conducted focus groups which provided qualitative data that supported the survey findings and revealed common themes including faculty perceptions of the relevance of bioinformatics in the curriculum. Despite the perceived value of bioinformatics education, many focus group members cited lack of student preparation and interest, and technological access as barriers. Participants also discussed how professional development and community support would enhance and sustain bioinformatics teaching. Taken together, this study indicates that challenges remain, which vary among faculty types and settings, but that more educators are attempting to integrate bioinformatics into life sciences education. In summary, our results suggest that redoubled efforts to provide training and community support to life sciences faculty is necessary.